Roots and fruits : retrieving Scotland's missionary story - Ross, Kenneth R. (Fortress Press, 2014)
Scotland has played a major role in the worldwide movement of Christian mission. Equally, the missionary movement has played a big part in Scotland's story. There have been many studies of particular people, places, and periods that feature in this story. The distinctive contribution of this book is its attempt to offer a comprehensive and synchronic assessment of the movement as a whole. It examines the development of Scottish mission theory and practice from the formation of the Society in Scotland for the Propagation of Christian Knowledge in 1709 until the present day. It explores some of the leading features of the movement through original analysis from leading scholars in the field. The essays that compose this volume increase understanding of a dimension of Scotland's story that is often overlooked or forgotten. They also contribute to our understanding of the modern missionary movement and suggest lessons that can be learned by those taking fresh mission initiatives in many different contexts today.